Metabolic Traits in Cutaneous Melanoma - Neagu, Monica (Frontiers in Oncology, 2020)
Tumour microenvironment is a network of complex cellular and molecular systems where cells will gain specific phenotypes / specific functions that would drive tumorigenesis. In skin cancers, tumour microenvironment is characterized by tumor infiltrating immune cells that sustain immune suppression, mainly lymphocytes. Melanoma cellular heterogeneity can be described on various levels: genetics, proteomics, transcriptomic and metabolomic. Melanoma cells display a metabolic reprogramming triggered by both genetic alterations and adaptation to a microenvironment that lacks nutrients and oxygen supply. Tumor cells present clear metabolic adaptations and identifying deregulated glycolysis pathway could offer new therapy targets. Moreover the immune cells (T lymphocytes, macrophages, NK cells, neutrophils and so on) that infiltrate melanoma tumors have metabolic particularities that, upon interaction within tumor microenvironment, would favour tumorigenesis. Analyzing both tumor cell metabolism and the metabolic outline of immune cells can offer innovative insights in new therapy targets and cancer therapeutical approaches. In addition to already approved immune- and targeted therapy in melanoma, approaching metabolic check-points could improve therapy efficacy and hinder resistance to therapy.